The incidence of injuries in elite junior figure skaters - Dubravcic-Simunjak, S.; Pecina, M.; Kuipers, H.; Moran, J.; Haspl, M. (The American Journal of Sports Medicine, 2003)
Background: There has been rapid growth in the technical and physiologic demands made on skaters who perform more and more difficult jumps, spins, lifts, throws, and free skating movements. Purpose: To investigate the frequency of injuries and overuse syndromes in elite junior skaters. Study Design: Questionnaire. Methods: During four consecutive Junior World Figure Skating Championships and the Croatia Cup, we interviewed 236 female and 233 male skaters by questionnaire to determine the frequency of injuries and overuse syndromes. Results: Fifty-nine of the female skaters (25%) and 65 of the male skaters (27.9%) reported sustaining acute injuries; 101 female (42.8%) and 106 male (45.5%) skaters reported overuse syndromes. Low back pain was reported by 19 female and 23 male skaters. The most frequent acute injury was ankle sprain. In singles female skaters, the most frequent overuse injury was stress fracture (19.8%), followed by jumper`s knee (14.9%). In singles male skaters, jumper`s knee (16.1%) was the most frequent injury, followed by Osgood-Schlatter disease (14.2%). More than 50% of injuries in young singles figure skaters involved overuse syndromes. Pairs skaters and ice dance skaters had a higher risk of acute injury than overuse syndrome because of falls from lifts and throw jumps. Conclusions: Programs to improve postural alignment, flexibility, and strength, especially during the asynchronous period of bone and soft tissue development, should be instituted to prevent and reduce overuse syndromes.